(untitled) (Edma 0-6: Educación Matemática en la Infancia, 2022)
In this article we investigate the possibilities of the Concrete-Representational-Abstract-Integrated sequence as a teaching-learning methodology for addition and subtraction in the second grade of early childhood education. Specifically, we carried out an exploratory experience focused on a four-year-old student with language maturational delay and disruptive behavior. Individual sessions were organized according to the phases of the sequence, which were distributed as follows: initial evaluation, intervention, final evaluation, and maintenance. The student participated in all of them, and he was able to progressively perform addition and subtraction without prior knowledge. Moreover, this methodology was useful for the student to be able to maintain his performance four weeks after the intervention. Finally, we consider of interest the implications that this article may have for early childhood education teachers.